Psychological Reactance and Beliefs in Conspiracy Theories During the Covid-19 Pandemic: Overview of the Extended Parallel Process Model (EPPM) - Bartolomeus Yofana Adiwena; Monika Windriya Satyajati; Widawati Hapsari (Buletin Psikologi, 2020)
Compliance with health protocols plays an important role in minimizing the spread of Covid-19. However, Indonesia is still facing a robust challenge including non-compliance to persuasive recommendations or messages (psychological reactance) and belief in conspiracy theories. Issues related to conspiracy theories and theories had obscured the message for the people to keep their behavior safe from the virus. The Extended Parallel Process Model (EPPM) is a theory that explains how people would obey the messages they received, particularly health messages. Perception of threats and efficacy contribute significantly to the effectiveness of the message people received. In this article, we discussed four psychological conditions that possess the chance to affect society's threats and efficacy to comply with health protocols. These conditions were viewed from social, clinical, and industrial-organizational psychology perspectives. Four solutions to cope with non-compliance tendencies were also proposed. We suggest that these solutions should be applied to strengthen the tendency for people to obey health protocols.